New Insights Into the Circadian Rhythm and Its Related Diseases - Xie, Yanling; Tang, Qingming; Chen, Guangjin; Xie, Mengru; Yu, Shaoling; Zhao, Jiajia; Chen, Lili (Frontiers in Physiology, 2019)
Circadian rhythms (CR) are a series of endogenous autonomous oscillators generated by the molecular circadian clock which serve to coordinate internal time with the external environment in a 24-h daily cycle. The circadian clock system is a major regulatory factor for nearly all physiological activities and its disruption has severe consequences on human health. CR disruption is a common issue in modern society, and studies on shift workers have shown that CR disruption can lead to cognitive impairment, psychiatric illness, metabolic syndrome, dysplasia, and cancer. In this review, we summarized the synchronizers and the synchronization methods used in experimental research, and introduced CR monitoring and detection methods. Moreover, we evaluated conventional CR databases, and analyzed experiments that characterized the underlying causes of CR disorder. Finally, we further discussed the latest developments in understanding of CR disruption, and how it may be relevant to health and disease. Briefly, this review aimed to synthesize previous studies to aid in future studies of CR and CR-related diseases.